Musicians as teachers: Developing a positive view through collaborative learning partnerships - Bennett, Dawn; Stanberg, A. (SAGE publishers, 2007)
Previous research with classical instrumental musicians has highlighted the intrinsic benefits of teaching in addition to the perhaps more obvious benefits of securing a regular income, and yet despite the presence of educational activities in the portfolio of most musicians it remains on the periphery of many music performance programs. The hierarchical inference in musicians? self-report of success as a soloist, instrumentalist or teacher is perpetuated in the separation of education and performance students during their university education. This study investigated the effects of providing a positive engagement with teaching through a unit of study delivered to a combined cohort of 2nd year undergraduate music education, composition and performance students. The unit was designed to increase students? understanding of the realities of professional practice, and to form productive and mutually beneficial partnerships: promoting a better appreciation of career development and self-identity during the formative years of study. Students? responses were gauged with the use of surveys implemented at the commencement and conclusion of the unit. Performance and composition majors reported a positive change in their perception of the role of teaching in their careers, and music education majors reflected a growing awareness of the benefits of working in partnership with performers. The study demonstrated that positive teaching experiences within the training of musicians, increases the likelihood that students will plan a positive engagement with teaching.